Stunting: an overlooked problem in Myanmar – an economic evaluation. (20th April 2020) - Aye, San Kyu Kyu; Mar, Swe Le; Lwin, Nyi Nyi; Hnin, Zar Lwin; Hlaing, Lwin Mar; Washington, Michael L.; Harris, Julie R.
Abstract: Objectives: Stunting increases a child's susceptibility to diseases, increases mortality, and is associated over long term with reduced cognitive abilities, educational achievement, and productivity. We aimed to assess the most effective public health nutritional intervention to reduce stunting in Myanmar. Methods: We searched the literature and developed a conceptual framework for interventions known to reduce stunting. We focused on the highest impact and most feasible interventions to reduce stunting in Myanmar, described policies to implement them, and compared their costs and projected effect on stunting using data-based decision trees. We estimated costs from the government perspective and calculated total projected cases of stunting prevented and cost per case prevented (cost-effectiveness). All interventions were compared to projected cases of stunting resulting from the current situation (e.g., no additional interventions). Results: Three new policy options were identified. Operational feasibility for all three options ranged from medium to high. Compared to the current situation, two were similarly cost-effective, at an additional USD 598 and USD 667 per case of stunting averted. The third option was much less cost-effective, at an additional USD 27, 741 per case averted. However, if donor agencies were to expand their support in option three to the entire country, the prevalence of 22.5 percent would be reached by 2025 at an additional USD 667 per case averted. Conclusions: A policy option involving immediate expansion of the current implementation of proven nutrition-specific interventions is feasible. It would have the highest impact on stunting and would approach the WHO 2025 target.